A qualitative research synthesis of positive subjective experiences in occupation from the Journal of Occupational Science (1993–2010). Issue 3 (3rd July 2018) - Eakman, Aaron M.; Atler, Karen E.; Rumble, Morgan; Gee, Bryan M.; Romriell, Brittney; Hardy, Natalie
ABSTRACT: Meaning in occupation is an essential concept for occupational science because its presence is thought to foster human development, health, and well-being. We explored this concept using qualitative research synthesis and integrated 11 qualitative studies of meaning in occupation from the Journal of Occupational Science published between 1993 and 2010. Framework synthesis method guided data extraction and focused on identification of positive subjective experiences associated with occupation. Content analysis method guided interpretation of the framework synthesis data, from which a richly interconnected system of positive subjective experiences (forms of meaning) emerged, referred to as an occupational meaning system. The higher-order themes of Social, Selfhood, and Pleasure meanings were frequently linked together by their 12 underlying forms of meaning: belonging and helping ( Social ), autonomy, mastery, continuity, self-esteem, health and well-being, and purposes ( Selfhood ), and enjoyment, stimulating, and satisfaction ( Pleasure ). Study findings advance an understanding of the interrelated nature of multiple meanings associated with occupation. Use of an occupational meaning system can provide researchers a framework for the study of meaning and change in meaning in occupations nested within sociocultural contexts.